IMPROVEMENT OF THE MECHANISM OF IMPLEMENTATION OF REGIONAL STATE PROGRAMS - V. Borozenets; D. Nikulina (Вестник Северо-Кавказского федерального университета)
The article discusses new approaches that contribute to ensuring the efficiency of budget expenditures at the regional level. The problems of implementation of target program budgeting in the context ofprocess automation are identified. The solution of the identified problems will allow the formation of clear algorithms in public financial management at the regional level and in the future will make it possible to use the digitalization mechanisms in full. The study substantiates the proposal to organize, on the basis of the Ministry of Finance of the Stavropol Territory, the creation of a single center for the operational processing of information on state programs and deines the regulations of its structural divisions.